Top-Ten Tips for Imaging the Triangular Fibrocartilaginous Complex - Ng, Alex W.H.; Tong, Cina S.L.; Hung, Esther H.Y.; Griffith, James F.; Tse, W.L; Wong, Clara W.Y.; Mak, Michael C.K.; Ho, P.C (Seminars in Musculoskeletal Radiology, 2019)
The triangular fibrocartilage complex (TFCC) is a crucial structure for both maintaining the stability of the distal radioulnar joint (DRUJ) and acting as a cushion for axial loading of the ulnocarpal joint. Injury to the TFCC can lead to early degeneration of the DRUJ and ulnocarpal joint, with resultant chronic wrist pain and weakness. The TFCC is a moderately complex structure with several attachments to the adjacent bony and cartilaginous structures. Familiarity with the anatomy of the TFCC is a prerequisite for identification of TFCC tears. Several pitfalls can occur while assessing the TFCC on magnetic resonance imaging (MRI) if one is not familiar with the MRI appearances. This article illustrates key tips for diagnosing TFCC tears on MRI.
Keywords: TFCC; wrist; arthrogram; traction; MRI